Admission and Readmission/Death Patterns in Hospitalized and Non-hospitalized First-Ever-in-a-Lifetime Stroke Patients During the First Year: A Population-Based Incidence Study - Abreu, Pedro; Magalhães, Rui; Baptista, Diana; Azevedo, Elsa; Correia, Manuel (Frontiers in Neurology, 2021)
Background. Hospitalization and readmission rates after a first-ever-in-a-lifetime stroke (FELS) are considered measures of quality of care and, importantly, may give valuable information to better allocate health-related resources. We aimed to investigate the hospitalization pattern and the unplanned readmissions or death of hospitalized and non-hospitalized stroke patients one year after a FELS, based on a community register. Methods. Data about hospitalization and unplanned readmissions and case fatality one year after a FELS were retrieved from the population-based register undertaken in Northern Portugal (ACIN2), comprising all FELS in 2009-2011. We used the Kaplan-Meier method to estimate one-year readmission/death-free survival and Cox proportional hazard models to identify independent factors for readmission/death. Results. Of the 720 FELS, 35.7% were not hospitalized. Unplanned readmission/death within one year occurred in 33.0% and 24.9% of hospitalized and non-hospitalized stroke patients, respectively. The leading causes of readmission were infections, recurrent stroke, and cardiovascular events. Stroke-related readmissions were observed in more than half of the patients in both groups. Male sex, age, pre- and post-stroke functional status, and diabetes were independent factors of readmission/death within one year. Conclusion. About one-third of stroke patients were not hospitalized, and the readmission/death rate was higher in hospitalized stroke patients. Still, that readmission/death rate difference was likely due to other factors than hospitalization itself. Our research provides novel information that may help implement targeted health-related policies to reduce the burden of stroke and its complications.